2007
DOI: 10.2139/ssrn.868395
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Event Studies With Asia-Pacific Security Market Data

Abstract: We investigate the effectiveness of standard event study procedures with Asia-Pacific security returns data. Monte Carlo simulation experiments reveal that standard event study test statistics often exhibit modest misspecification under a null hypothesis of no abnormal performance. This holds for both parametric and nonparametric tests. Test misspecification is severe with clustered event dates or a doubled event date returns variance.JEL Classification: C12, C14, C15, G14, G15 Conducting Event Studies With A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 41 publications
0
48
0
1
Order By: Relevance
“…In simulation experiments based on New York stock exchange data, Boehmer et al (1991) and Corrado and Truong (2008) report that this test statistic is well specified with good power properties.…”
Section: 'Brown and Warner' Methodology Studiesmentioning
confidence: 96%
See 3 more Smart Citations
“…In simulation experiments based on New York stock exchange data, Boehmer et al (1991) and Corrado and Truong (2008) report that this test statistic is well specified with good power properties.…”
Section: 'Brown and Warner' Methodology Studiesmentioning
confidence: 96%
“…The most successful among these tests were the nonparametric sign and rank tests advanced in McConnell and Muscarella (1985), Corrado (1989), Lummer and McConnell (1989), Zivney and Thompson (1989), and Corrado and Zivney (1992). Well-known studies of this type are Chandra et al (1992Chandra et al ( , 1995, Cowan (1992Cowan ( , 1993, Wasley (1993, 1996), Cowan and Sergeant (1996), Giaccotto and Sfiridis (1996), Affleck-Graves et al (2000), Dombrow et al (2000), Seiler (2000), Bartholdy et al (2007), and Corrado and Truong (2008). These studies generally concluded that sign and rank tests are well specified and provide an improvement in test power compared to standard parametric tests.…”
Section: 'Brown and Warner' Methodology Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…While the metric proposed by Brown and Warner (1985) is a parametric test statistic, the metric developed by Corrado (1989) is a rank-based nonparametric test statistic. For a discussion of the statistical advantages and attributes of these specific test statistics, see Warner (1980, 1985) and Corrado and Zivney (1992), Corrado and Truong (2008).…”
Section: Determinants Of Stock Market Reactionsmentioning
confidence: 99%